Penetrasi Fotovoltaik dengan Metode MILP dan Pertimbangan Pembebanan Minimal Teknis - Alfi Bahar; Muhammad Yasirroni; Sarjiya; M. Isnaeni Bambang Setyonegoro (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
Technological development and the reduction of installation costs have caused a rapid growth of solar power plants in Indonesia. The National Electricity Company (Perusahaan Listrik Negara, PLN) strives to achieve the energy mix of renewable energy to 23% by 2025. Solar power plants are unique in that they only supply their power during the daytime. It makes solar power plants connected to the power system change the load profile of the Java-Bali system. In this study, the penetration of solar power plants changed the scheduling of the Java-Bali system because the penetration was installed to the technical minimum loading of existing power plants. When penetration is too big, thermal generator scheduling failure is possible. Unit commitment and economic dispatch with mixed-integer linear programming (MILP) method using CPLEX and Python were carried out to calculate the fuel and generation costs per kWh before and after the penetration. MILP was used to solve the cost fuel equation, namely an integer and nonlinear mix equations, that are challenging to be solved using standar nonlinear programming methods. Due to the use of the MILP-UC, all objective function equations and restraint functions must be linear functions. The tests were conducted for three years, from 2023 to 2025. Simulation results on the Java-Bali system show that the capacity of solar power plants penetrating the Java-Bali system against the peak load will be 52%, 52%, and 50% in 2023, 2024, and 2025, respectively. Meanwhile, penetration of solar power plants to technical minimum loading of existing power plants resulted in the fuel cost falling by 23% in 2023 and 22% in 2024 and 2025. Lastly, the cost of generation per kWh will be decreased by 8% in 2023 and will be as low as 7% in 2024 and 2025.